Quilombolas e Trajetórias de Escolarização: um Estudo a Partir de Retiro, Santa Leopoldina–ES. - Kill, Paula Aristeu Alves (2020)
The Quilombola community of Retiro, located in the municipality of Santa Leopoldina (ES), is the place WHERE the fieldwork for the elaboration of this masters thesis is carried out. The main aim is to analyze the schooling trajectories built and narrated